Efektivitas Penerapan Model STAD berbantuan Quizizz terhadap Kemampuan Numerasi Matematika Materi Perkalian Siswa SD - Elda Olivia Rossalia; Wulan Sutriyani (JANACITTA, 2025)
Abstract This study aims to examine the differences in students' numerical abilities before and after the implementation of the Student Teams Achievement Division (STAD) cooperative learning model, as well as the effectiveness of integrating the model with the digital Quizizz platform in improving students' numerical abilities in elementary schools.  This study uses a quantitative approach with a pre-experimental design, namely the one-group pretest-posttest model. The instruments used include a learning module and 20 validated questions to assess students' abilities through initial and final exams. The results of data analysis show a significant increase in students' numeracy abilities, with an average pretest score of 44.80 and a posttest score of 79.20. The t-test shows that the calculated t-value of 8.684 is greater than the t-table value of 2.064, with a p-value of 0.000, which is below the significance threshold of 0.05. The calculated t value of 8.684 is greater than the t-table value of 2.064, with a p-value of 0.000, which means it is below the significance value of 0.05. Based on these results, the null hypothesis (H₀) is rejected and the alternative hypothesis (Hₐ) is accepted. It can be concluded that the application of the STAD model based on the Quizizz platform is able to significantly improve the mathematical numeracy skills of elementary school students. Abstrak Penelitian ini bertujuan untuk mengkaji perbedaan kemampuan numerasi siswa sebelum dan sesudah diterapkannya model pembelajaran kooperatif Student Teams Achievement Division (STAD ), serta efektivitas integrasi model tersebut dengan platform Quizizz digital dalam meningkatkan kemampuan numerasi siswa di sekolah dasar.​​​​ Populasi dalam penelitian ini adalah siswa/siswi kelas II SDN 1 Tahunan yang berjumlah 25 peserta didik dan sampel yang digunakan sampel jenuh dalam pengambilan sampel. Penelitian ini menggunakan pendekatan kuantitatif dengan desain pra-eksperimental, yaitu model one group pretest-posttest. Instrumen yang digunakan meliputi modul pembelajaran dan 20 soal yang telah divalidasi untuk menilai kemampuan siswa melalui ujian awal dan akhir. Hasil analisis data menunjukkan adanya peningkatan yang signifikan dalam kemampuan numerasi siswa, dengan rata-rata skor pretest sebesar 44,80 dan skor posttest sebesar 79,20. Uji-t menunjukkan nilai t-hitung sebesar 8,684, lebih besar dari nilai t-tabel sebesar 2,064, dengan nilai p sebesar itu​ yang berada di bawah ambang signifikansi 0,05. Nilai t-hitung sebesar 8,684 lebih besar dibandingkan dengan nilai t-tabel sebesar 2,064, dengan nilai p sebesar 0,000 yang berarti berada di bawah nilai signifikansi 0,05. Berdasarkan pada hasil tersebut hipotesis nol (H₀) ditolak dan hipotesis alternatif (Hₐ) diterima. Dapat disimpulkan bahwa penerapan model STAD yang berbasis platform Quizizz mampu meningkatkan kemampuan numerasi matematika siswa sekolah dasar secara signifikan.​​​​​​